Rideshare use among parents and their children - Johnathon P. Ehsani; Jeffrey P. Michael; Andrea Gielen (BMC, 2021)
Abstract Motor vehicle crashes are the leading cause of death for young children. Millions of ridesharing trips are taken each day, and use of these services is predicted to increase. Therefore, it is important to examine the safety of children in these vehicles. We conducted a survey of a nationally representative sample of U.S. adults aged 18 years or older (N = 2017). Of the total sample, 450 respondents reported being a parent or legal guardian of children below the age of 10. Of these, 307 or 68% had ever used ridesharing. Among those who had used ridesharing, a total of 253 or 82% reported using ridesharing with their children below the age of 10 years. Among this group, rideshare use was significantly higher among individuals with college education, and in higher income households. Given that the majority of U.S. states have legislation exempting rideshare vehicles from child restraint system law coverage, our finding of high rates of rideshare use among parents suggests that a large number of children could be at risk of injury due to a lack of appropriate restraint use.